Extracellular Vesicles Secreted by TGF-β1-Treated Mesenchymal Stem Cells Promote Fracture Healing by SCD1-Regulated Transference of LRP5 - Zihui Zhou; Chenyang Guo; Xulong Sun; Zhengwei Ren; Jie Tao (Stem Cells International)
Bone fracture repair is a multiphased regenerative process requiring paracrine intervention throughout the healing process. Mesenchymal stem cells (MSCs) play a crucial role in cell-to-cell communication and the regeneration of tissue, but their transplantation is difficult to regulate. The paracrine processes that occur in MSC-derived extracellular vesicles (MSC-EVs) have been exploited for this study. The primary goal was to determine whether EVs secreted by TGF-β1-stimulated MSCs (MSCTGF-β1-EVs) exhibit greater effects on bone fracture healing than EVs secreted by PBS-treated MSCs (MSCPBS-EVs). Our research was conducted using an in vivo bone fracture model and in vitro experiments, which included assays to measure cell proliferation, migration, and angiogenesis, as well as in vivo and in vitro gain/loss of function studies. In this study, we were able to confirm that SCD1 expression and MSC-EVs can be induced by TGF-β1. After MSCTGF-β1-EVs are transplanted in mice, bone fracture repair is accelerated. MSCTGF-β1-EV administration stimulates human umbilical vein endothelial cell (HUVEC) angiogenesis, proliferation, and migration in vitro. Furthermore, we were able to demonstrate that SCD1 plays a functional role in the process of MSCTGF-β1-EV-mediated bone fracture healing and HUVEC angiogenesis, proliferation, and migration. Additionally, using a luciferase reporter assay and chromatin immunoprecipitation studies, we discovered that SREBP-1 targets the promoter of the SCD1 gene specifically. We also discovered that the EV-SCD1 protein could stimulate proliferation, angiogenesis, and migration in HUVECs through interactions with LRP5. Our findings provide evidence of a mechanism whereby MSCTGF-β1-EVs enhance bone fracture repair by regulating the expression of SCD1. The use of TGF-β1 preconditioning has the potential to maximize the therapeutic effects of MSC-EVs in the treatment of bone fractures.